Reconstruction of Wind Velocity Distribution Using POD Model. (November 2016) - Sun, Ying; Sun, Shanxun; Zhang, Jingyin; Liu, Shi
Abstract: The proper orthogonal decomposition (POD) has been widely used in fluid dynamic applications for extracting dominant flow features, can reconstruct the entire flow field according to a limited number of measured data. In this paper, the POD was used to reconstruct the velocity distribution of the wind field, and the effectiveness is evaluated by simulation. The sensitivity and accuracy of the reconstruction results versus the numbers of measured data are analyzed. The simulation results show that by using the dominant POD modes and a limited number of sensors, the reconstruction can yield reasonably accurate velocity distribution results.